Approaches to dual VET in tertiary education in South Korea - Hanau, Eva [Verfasser]; Jeon, Seung-Hwan [Verfasser]; Lee, Han-Byul [Verfasser] (My University, 2019)
"In South Korea, state reforms aim to strengthen the quality and attractiveness of vocational education and training (VET). Dual elements have been introduced in secondary and tertiary education and initial steps have been taken to improve the permeability between educational sectors and to strengthen the practical orientation of higher education. On the basis of two programmes, the article illustrates the concrete implementation as well as structural framework conditions of these policies and points out perspectives and challenges." (Author's abstract ; BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; S 1.4 Hochschulbildung; I 2.3.4 Asien; Berufsbildungssystem; Berufsbildung; Hochschulbildung; Durchlässigkeit im Bildungssystem; Südkorea